Pengaruh Profitabilitas, Likuiditas, Konservatisme Akuntansi, dan Modal Intelektual terhadap Kualitas Laba - Vania Magdalena; Estralita Trisnawati (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
This purpose of this study is to analyze the effect of profitability, liquidity, accounting conservatism, and intellectual capital on earning quality. This research was conducted on primary consumer goods sector company that are listed on IDX from 2018-2020, the samples were selected using purposive sampling method and 33 companies were acquired as valid data. The data collected were processed using Microsoft Excel 2019 and software Eviews 12. The analysis results showed that profitability, liquidity, accounting conservatism, and intellectual capital simultaneously have a significant effect on earning quality. Individually, profitability, liquidity, and intellectual capital do not have effects on earning quality. While, accounting conservatism has a negative effect on earning quality.